Effectiveness of the Problem-Based Learning Model Assisted by VBA-Based Media for Excel in Equivalency Education Context - Nurhayati, Sri; Taufikin, Taufikin; Chotimah, Siti (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study investigates the effectiveness of a Problem-Based Learning (PBL) model, augmented by Visual Basic for Applications (VBA) for Excel, in enhancing students' mathematical understanding and skills. PBL emphasizes problem-solving, while VBA for Excel is a programming tool utilized for automating tasks within Excel spreadsheets. The study was conducted amongst a group of students at the elementary level equivalency education. Data were collected through pre and post-tests, classroom observations, and student feedback on the use of the PBL model and VBA for Excel. The results indicate a significant improvement in students' mathematical understanding and skills using the PBL model supported by VBA for Excel.  Participants exhibited a marked enhancement in their ability to develop mathematical skills. Additionaly, student satisfaction surveys revealed a positive response to the integration of PBL and VBA for Excel, reporting higher motivation, deeper engagement, and a positive perception of the relevance of the learning material. This research provides evidence that combining PBL and VBA for Excel can be an effectivite approach and medium for mathematics education, underscoring the importance of integrating real problem-solving using relevant technological applications in the process. The practical implication is that a VBA for Excel supported PBL model can foster enhanced understanding and skills in mathematics.